Visions of an Ancient Ethiopian Church and the Africanization of Catholic History in José Antonio Aponte's Afro-Cuban Codex. - Ojeda in collaboration with Miriam Franchina, Jorge Pavez (Slavery & Abolition, 2025)
In 1812, the trial of the insurgents involved in an antislavery rebellion in Cuba centred on a book of images found in the home of its author and alleged leader, José Antonio Aponte. As a unique and now lost Afro-Cuban codex, the archival descriptions of its plates provide an inexhaustible source for the study of Afro-Latin art and religious history. This article reconstructs the Catholic imagery mobilized by Aponte, focusing on three key aspects. First, the importance of the Catholic Enlightenment and its reform agenda for abolitionism in Cuba at the turn of the eighteenth and nineteenth centuries; second, the ancient Christian kingdom of Prester John in Ethiopia and its connections to European kingdoms and the Catholic Church as inspiration for Black insurgents to challenge the legitimacy of evangelization through enslavement; and third, the crucial role played by Catholic Haiti, as heir to the Ethiopian kingship, and an example of Black sovereignty in encouraging freedom movements and feelings of dignity among Africans and Afro-descendants.